Russian company investment project valuation with the built-in abandon option - D. V. Vorotnikova; M. E. Detkova; M. A. Khalikov (Путеводитель предпринимателя)
This paper is dedicated to development of models and numerical methods for evaluating investment projects of Russian companies using the real options model. In the current economic conditions, it is highly necessary to properly reflect the flexibility of the company’s in adapting management decisions in response to changing market conditions. In this regard, the traditional models of investment analysis can be supplemented, and in some cases replaced by alternative approaches, for example, by estimating the present value of a call (put) option using the Black-Scholes-Merton formula. The above given statement determines the relevance of the study. The paper presents theoretical and practical aspects of the use of traditional and optional approaches to the evaluation of investment projects. It also presents practical calculations for investment project related to implementation of automated information system for compiling consolidated statements for a group of companies whose assessments need to take into account a real option to abandon the project.